In-Car Air Quality Notification Using Internet of Things Platform - Regi Fernando Najoan; Suharjito Suharjito (Bina Nusantara University, 2023)
In the development of modern society, transportation is essential to support daily activities. With the existence of vehicles, the activities carried out by the community will be much easier. The car is a means of transportation that is often used by the community to carry out activities related to their respective goals. In-car air quality is very crucial for society because most people spend their time in cars. Often, the air in the car contains not only good air but also bad air for humans. The impact of poor air quality can make people sleepy, as well as cause respiratory problems and several other diseases that can even affect a driver's ability to make decisions. Therefore, there must be a real-time monitoring and notification system for air quality in the car. The purpose of this research is to be able to develop an air quality monitoring system for cars and provide notifications if the air quality worsens in real-time. In this study, researchers developed an air quality monitoring and notification system for cars using the NodeMCU ESP8266 microcontroller, sensors MQ-7, MQ-135, PMS5003, and the IoT platform, namely Blynk and ThingSpeak. The result of this research is a system that can detect, measure, and monitor air quality levels of carbon dioxide (CO), carbon monoxide (CO2), particulate matter (PM10), and particulate matter (PM2.5) via the internet in real-time. and displays air quality data on the dashboard, then provides notifications using the Blynk application if the air quality is low and getting worse.